Nepal’s Portrayal of Its International Image - Adhikari, Sudip (Unity Journal, 2024)
This paper examines the evolution of Nepal's national identity in the modern context, moving beyond its traditional associations with stunning mountains, Buddha's birthplace, and Gurkha bravery. The study argues that Nepal's portrayal on the global stage is a complex interplay of ancient narratives, diplomatic engagements, and evolving national identity, all influencing its global status. The methodology employs historical analysis to explore Nepal's interactions with other nations, emphasizing the role of its Cold War-era strategic neutrality in shaping its diplomatic stance. Additionally, it analyzes documents to track changes in self-presentation, considering cultural aspects, tourism promotion, and humanitarian efforts as tools for crafting a positive global image. It further explores Nepal's involvement in UN peacekeeping, multilateral forums, and regional dynamics to illuminate the connection between self-presentation and diplomatic goals. Ultimately, the research underscores the importance of a comprehensive diplomatic strategy that aligns with Nepal's national interests and cultural heritage, enabling effective navigation of the complex global landscape while safeguarding its sovereignty.